Widening the gap: Unequal distribution of resources for K–12 science instruction - Smith, P. Sean; Trygstad, Peggy J.; Banilower, Eric R. (Education Policy Analysis Archives, 2016)
Inequalities in educational opportunity are well documented. Regardless of the nature of the disadvantage—low income, underrepresented minority status, or prior achievement—students from backgrounds associated with a given disadvantage have less access to educational opportunities. In this article, we use data from the 2012 National Survey of Science and Mathematics Education to explore how resources are allocated for science instruction specifically. We focus on how three kinds of resources—well-prepared teachers, material resources, and instruction itself—are allocated to classes that are homogeneously grouped by prior achievement level. Regardless of the resource, we find that classes of students with low prior achievement (as perceived by their teachers) have less access. Some of the differences are striking, particularly regarding access to material resources, while others are more subtle. There is also evidence that some policies do not impact teachers equally. For example, time allowed for teacher professional development is perceived differently by teachers in terms of its impact depending on the achievement level of students in the class. The study supports the assertion that what is known about ability grouping in general applies in science instruction specifically. When students with low prior achievement are grouped together, their classes have less access to critical resources for science learning opportunities, potentially widening the gap between them and their higher-achieving peers.